Toxicity evaluation of the landfill leachate after treatment with photo-Fenton, biological and photo-Fenton followed by biological processes. Issue 4 (21st March 2019) - Colombo, Andréia; Módenes, Aparecido N.; Trigueros, Daniela E. G.; de Medeiros, Bruna L.; Marin, Pricila; Monte Blanco, Silvia P. D.; Hinterholz, Camila L.
Abstract: The objective of this study was the toxicity evaluation of landfill leachate samples both raw and after treatment by photo-Fenton (PF), biological (Bio) and photo-Fenton followed by biological (PF-Bio) processes. The organisms Artemia salina and Lactuca sativa were exposed to the leachate in different dilution. In the phytotoxicity evaluation, the inhibition of root (RGI) and radicle (RAGI) growth, and the number of germinated seeds (GR) were evaluated. In the ecotoxicity analysis, the 50% lethal dose (LD50 ) for each type of treatment was evaluated. The raw leachate, and after treatments PF, Bio and PF-Bio presented COD of 12, 797, 1, 347, 1, 685, 220 mg/L and BOD5 of 4, 251, 1, 060, 692 and 89 mg/L, respectively. The GR was 0, 95, 25 and 40%, RGI was 100, 83, 100, 93%, whereas RAGI was 100, 72, 100 and 79% in the raw leachate and after treatments PF, Bio and PF-Bio, respectively. LD50 values of 0.25, 0.40, 0.38 and 0.54 were obtained for the raw effluent and after the PF, Bio and PF-Bio treatments, respectively. Smaller values of COD, BOD5, ecotoxicity and phytotoxicity were observed in the effluent after the PF-Bio treatment, indicating that this is the most environmentally suitable system for the treatment of landfill leachate.